The measurement of physical functioning among patients with Tenosynovial Giant Cell Tumor (TGCT) using the Patient-Reported Outcomes Measurement Information System (PROMIS) - Heather L. Gelhorn; Xin Ye; Rebecca M. Speck; Sandra Tong; John H. Healey; Susan V. Bukata; Richard D. Lackman; Lindsey Murray; Grant Maclaine; William R. Lenderking; Henry H. Hsu; Paul S. Lin; et al. (SpringerOpen, 2019)
Abstract Background Tenosynovial giant cell tumor (TGCT), a rare, locally aggressive neoplasm of the synovium of joints and tendon sheaths, is associated with joint destruction, pain and swelling. Impacts on physical function (PF) vary depending on tumor size and location. The aim of this study was to identify relevant items, and demonstrate the content validity of custom measures of lower extremity PF from the Patient-Reported Outcomes Measurement Information System Physical Function Physical Function (PROMIS-PF) item bank among patients with TGCT. Methods Patients were recruited for qualitative research interviews to identify predominant TGCT symptoms and impacts. Patients completed a checklist to evaluate the relevance of each PROMIS-PF item. The publicly available PROMIS-PF item response theory (IRT) parameters were used to select items representing the range of the latent PF trait. Results Participants (n = 20) were 75% female, mean age 42.5 years. TGCTs were located in the knee (n = 15), hip (n = 3), and ankle (n = 2). Fifty-four PROMIS-PF items were identified as relevant by ≥20% of the participants. PF concepts discussed by participants during the qualitative interviews were also used to select relevant items. Selected items (n = 13) were used to create a physical function subscale specific to lower extremity tumors. Conclusions We describe a novel method of combining qualitative research and IRT-based item information to select a relevant and content valid subset of PROMIS-PF items to assess heterogeneous impacts on PF in TGCT, a rare disease population.